Exploring the views of Malaysian scholars on knowledge production in the social science - Abdulra’Uf, M.Y. (American Scientific Publishers, 2017)
This article explores the views of Malaysian social scientist on the state of the art of social science production in Malaysia. It aims at understanding the perspective of seasoned academics regarding the scholarly tradition of social science in the context of Burawoy’s idea of Public sociology. The paper adopts a qualitative research paradigm using a phenomenological approach in eliciting the responses. A purposive interview was conducted with four Malaysian scholars in the five Malaysian research universities. The scope of the paper is confine to epistemological challenge posed by the positivist inclination of the social sciences in Malaysia. The paper suggests a major shift in Malaysian social science landscape, from what appears to be a critical public discourse in the Universities, to a search for professional discourse excellence. We adopted Burawoy’s notion of ‘public sociology’ in explicating this intellectual shift. Our data suggests that the search for professional excellence and the aspiration to be a world-class university has inhibit the potentials of social scientist to engage in Critical public discourse in the social science. © 2017 American Scientific Publishers. All rights reserved.